2013
DOI: 10.1007/s10654-013-9761-7
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive pulmonary disease in old age among individuals born preterm

Abstract: There are only few studies of the association between preterm birth and risk of chronic lung disease in old age. The aim of this study was to assess the association between poor fetal growth, preterm birth, sex and risk of asthma and Chronic Obstructive Pulmonary Disease (COPD) in adulthood. We have followed up a cohort of all infants born preterm (<35 weeks) or with low birth weight (<2,000 and <2,100 g for girls and boys, respectively) and an equal number of controls in a source population of 250,000 individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
52
3
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(60 citation statements)
references
References 21 publications
4
52
3
1
Order By: Relevance
“…Lower birth weights in infants born preterm may be a factor; in a population-based case-control study an increased risk of hospitalisation for respiratory disease in adults with low birth weight compared to those with normal birth weight was reported [27]. In a recently reported population-based cohort study, low birth weight and preterm birth were identified as risk factors for the presence of obstructive airway disease in old age [28].…”
Section: Discussionmentioning
confidence: 97%
“…Lower birth weights in infants born preterm may be a factor; in a population-based case-control study an increased risk of hospitalisation for respiratory disease in adults with low birth weight compared to those with normal birth weight was reported [27]. In a recently reported population-based cohort study, low birth weight and preterm birth were identified as risk factors for the presence of obstructive airway disease in old age [28].…”
Section: Discussionmentioning
confidence: 97%
“…Children with a history of prematurity have been shown to be at increased risk for obstructive lung disease 21 and cognitive deficits 22 , among other medical conditions. 23 This population has also been shown to be at risk for disorders affecting sleep, including increased rates of OSAS 3, 24 and differences in circadian rhythm.…”
Section: Discussionmentioning
confidence: 99%
“…The long-term clinical relevance of small to moderate lung function deficits in childhood related to preterm birth and perinatal events is not known. However, concern has been raised as to whether individuals born preterm, especially those born extremely preterm, may be at risk of developing COPD-like phenotypes later in life 30 . In addition, it is still unclear whether preterm birth is associated with a more rapid age-related decline in lung function in adulthood.…”
Section: Factors Affecting Lung Function Growthmentioning
confidence: 99%